Diets including Animal Food Are Associated with Gastroesophageal Reflux Disease - Luciana Baroni; Chiara Bonetto; Irene Solinas; Pierfrancesco Visaggi; Alexey V. Galchenko; Lucia Mariani; Andrea Bottari; Mattia Orazzini; Giada Guidi; Christian Lambiase; Linda Ceccarelli; Massimo Bellini; et al. (MDPI AG, 2023)
Gastroesophageal reflux disease (GERD) is a clinical condition with a prevalence of up to 25% in Western countries. Typical GERD symptoms include heartburn and retrosternal regurgitation. Lifestyle modifications, including diet, are considered a first-line therapeutic approach. To evaluate the impact of life habits on GERD in this cross-sectional study, we used data collected through an online survey from 1146 participants. GERD was defined according to the Montreal Consensus. For all participants, clinical and lifestyle characteristics were recorded. Overall, 723 participants (63.1%) consumed a diet including animal food (non-vegans), and 423 participants (36.9%) were vegans. The prevalence of GERD was 11% (CI 95%, 9-14%) in non-vegans and 6% (CI 95%, 4-8%) in vegans. In the multivariate analysis, after adjusting for confounding factors, subjects on a non-vegan diet were associated with a two-fold increase in the prevalence of GERD compared to vegans (OR = 1.96, CI 95%, 1.22-3.17, p = 0.006). BMI and smoking habits were also significantly associated with GERD. This study shows that an animal food-based diet (meat, fish, poultry, dairy, and eggs) is associated with an increased risk of GERD compared to a vegan diet. These findings might inform the lifestyle management of patients with GERD-related symptoms.